GEOGRAPHICAL BASIC FOR MANAGEMENT AND SUSTAINABLE USING AND ENVIRONMENT PROTECTION OF KON KA KINH NATIONAL PARK, GIA LAI PROVINCE - Quynh, Ha Quy (Vietnam Journal of Earth Sciences, 2014)
Study on the basic creation factors included: geology, geography, hydrology, climate and soil in National park for identifying the characteristic of each landscape ecology. This mission of scientific based have been studied for recommendation of management and sustainable using of natural resources in the National park. Kon Ka Kinh National Park is 41780 square ha, which is located in the North-east of Gai Lai province, belong to Đăk Roong, Kon Pne, Kroong communes (Kbang district); AJun (Mang Yang district) and Ha Dong commune (Đăk Đoa district). 183 The landscape ecology of Ka Ka Kinh National park is belong Tropical monsoon System of Vietnam, Subsystem of Topical monsoon in Tay Nguyen Highland. Belong to class of Mountain in Tay Nguyen highland, included 2 subclass (l) Low mountain and (2) Hill. There are 7 types of landscape ecology included: (1) Tropical Evergreen pine forest (2974.49 ha); (2) Tropical Evergreen broadleaf forest (8658.42 ha); (3) Tropical secondary evergreen broadleaf forest (19237.88 ha); (4) Plantation forest (129.45 ha); (5) Riverine forest (45.83 ha); (6) Scrub and grassland (9984.08 ha) and (7) Settlement and agriculture (1225.46 ha). The landscape ecology in Kon Ka Kinh National Park are habitats of 1022 species of plant; 79 species of mammal; 235 species of bird; 43 species of reptile and 39 species of amphibian. Because of the different of each creation factors, so that each landscape ecology have difference function, this scientific basic have been applied for management and development National park. Included: Conservation, reserve, environment protection function have been developed on landscape type I, II and III; 2) Forestry development have been developed on type IV and VI, below 700 m; 3) Exploitation function is in type III, IV and VI, below <1000m; Forest fire management have been developed in type III, IV and VI below <1300m; and 5) Scientific research, studying, ecotourism been developed in type landscape ecology I, II and III, elevation 700-1500m.ReferencesPhạm Hoàng Hải, Nguyễn Thượng Hùng, Nguyễn Ngọc Khánh, 1997. Cơ sở cảnh quan học của việc sử dụng hợp lý tài nguyên thiên nhiên bảo vệ môi trường lãnh thổ Việt Nam. Nxb. Giáo dục, Hà Nội. 160 trang.Vũ Tự Lập, 1999. Địa lý tự nhiên Việt Nam, Nxb. Giáo dục Hà Nội. 346 trang.Hà Quý Quỳnh, Lê Xuân Cảnh, 2009. Nghiên cứu cảnh quan ở Vườn quốc gia Chư Mom Ray, huyện Sa Thầy, tỉnh Kon Tum phục vụ bảo tồn Đa dạng sinh học. Báo cáo tại Hội nghị toàn quốc về những vấn đề nghiên cứu cơ bản trong khoa học sự sống 2009, Nxb. Khoa học và Kỹ thuật, Hà Nội, tr.1201-1206.Lê Bá Thảo, 2001. Việt Nam lãnh thổ và các vùng Địa lý, Nxb. Thế giới, Hà Nội, 612 trang.Thái Văn Trừng, 1999. Những hệ sinh thái rừng nhiệt đới ở Việt Nam, Nxb. Khoa học và Kỹ thuật, Hà Nội. 298 trang.Global USGS; Glovis; http://glovis.usgs.gov/